Pengaruh Systematic Strategic Planning dan Strategic Business Innovation terhadap Sustainable Performance UMKM: Studi Kasus pada UMKM Makanan dan Minuman kota Makassar - Muhammad Ilman Ramli Natsir; Abdul Rahman Kadir; Asty Almaida (Paulus Journal of Accounting (PJA), 2025)
This study aims to analyze the influence of systematic strategic planning and strategic business innovation on the sustainable performance of Micro, Small, and Medium Enterprises (MSMEs) in the food and beverage sector in Makassar City. The framework of this study refers to the concept of Triple Bottom Line and Resource-Based View. The research method used is a mixed method with a sequential explanatory design, involving 100 respondents in the quantitative stage and 5 sources in the qualitative stage. Quantitative data analysis was carried out using multiple linear regression, while qualitative data were analyzed using the Miles and Huberman model. The results of the study indicate that systematic strategic planning does not have a significant effect on the sustainable performance of MSMEs, while strategic business innovation has a positive and significant effect on the sustainable performance of MSMEs in Makassar City. The implications of this study are expected to provide insight for MSME entrepreneurs and policy makers in improving business sustainability through strategic business innovation.